Pengaruh Kinerja Pelayanan Terhadap Loyalitas Pelanggan - Devi Elvita; Tintin Suhaeni (Jurnal Riset Bisnis dan Investasi, 2017)
This study aims to determine the performance of services and customer loyalty mail and parcel as well as how much the influence of service performance to customer loyalty of mail and parcel in PT Pos Indonesia Bandung. Quota sampling technique was used to collect data through questionnaires to 115 people who use the services of courier mail and parcel post with Likert scale. The analysis method used is the multiple regression. The results showed that the performance of services in PT Pos Indonesia are in the category of good/high in terms of interaction quality, physical environment quality, and outcome quality. While customer loyalty mail and parcel that are in the category of average in terms of repeat purchase, purchases across product and service line, refers others and demonstrates immunity to the pull of the competition. The conclusion is the performance of services significantly affect customer loyalty mail and parcel in PT Pos Indonesia Bandung amounted to 54.7%.